Some Questions Related to Rao-Blackwellization and Association Rule Mining (International Journal of Statistical Sciences, 2024)
Prof. CR Rao has been awarded the prestigious 2023 International Prize in Statistics.  The citation reads: “In his remarkable 1945 paper published in the Bulletin of the Calcutta Mathematical Society, Calyampudi Radhakrishna (C.R.) Rao demonstrated three fundamental results that paved the way for the modern field of Statistics and provided statistical tools heavily used in science today……”. These three results are ‘Cramer-Rao Lower Bound’ (CRLB), ‘Rao- Blackwellization’ (RB) and the third one now flourished as ‘Information Geometry’. In this paper, we shall discuss two offshoots from his work over the eight decades. Several articles have appeared on his life and work (see for example, T. J. Rao (2019 and 2023a, 2023b) and Kumar (2023)).  The first offshoot is based on one of the three breakthrough results, namely, Rao–Blackwell Theorem, first proved by C.R. Rao in 1945, when he was just 25 years old and also by Blackwell later in 1947. The second one is on Association Rule Mining (ARM), which he developed when he was 96 years old. These two papers reveal the transition of statistical methodologies from Fisherian concepts to recent applications of AI and ML. In this paper we shall pose some questions which need further study.International Journal of Statistical Sciences, Vol.24(1), March, 2024, pp 85-89